Avaliação nutricional de misturas de feijão (Phaseolus vulgaris L.) e soja (Glycine max L.) processados por extrusão - Gomes Gualberto, Daisy; Hironaka Bicudo, Mitsue; Teixeira Coelho, Dilson; Maffia, Lúcia Maria; Milagres Teixeira, Sonia (Revista Ceres, 2025)
This research was conducted in the Food Technology and Nutrition Departments of Federal University of Vigosa, Minas Gerais, Brazil.